Quantitative analysis of the Income, Mental Health Effect of SARS COV-2 Pandemic in Calabar - Angioha, Pius U.; Ogar, James A.; Eteng, Eworo E.; Okpiliya, Godwin E.; Maruf, Gbadebo S.; Akintola, Abayomi; Ibioro, Francis E. (Daengku: Journal of Humanities and Social Sciences Innovation, 2021)
The novel SARS-COV-2 pandemic known as coronavirus (covid-19) pandemic has had such an impact that it has changed the way human behaves. Its impact has been felt in all sphere of human life. This study examines the extent to which the covid-19 pandemic has affected the socio-economic life of the people in Calabar, Cross River State, Nigeria. The survey research design was adopted in collecting data from 400 respondents from Calabar using cluster, purposive and simple random sampling technique. A self-developed questionnaire was used as the instrument of data collection. Descriptive statistics was used to analyse the data collected from the field. The result from descriptive analysis was also subjected to parametric statistics. Out of the 400 hundred instruments distributed 379 was returned and used for analysis. Result revealed that 89.2 percent report reduced income. 83.6 percent reported suffering as a result of income loss. 25.9 percent suffered from mental health issues. 14.2 percent reported needing to see a doctor. From the parametric statistics carried out, result revealed a significant correlation between covid-19 pandemic and family income and mental health. The study concludes that the covid-19 pandemic has significant impact in the life of people in Calabar. Based on this finding, there is a need for government to implement changes in social security programmes as well as provide guidance and advice for health workers and general public etc